Stolen sisters - Kuzio, Katelyne; Fleury, Jade; Garcia, Jessa (My University, 2019)
“Stolen Sisters” is a powerful digital story which outlines the colonial impacts on Indigenous people which has contributed to the contemporary issue of Missing and Murdered Indigenous Women and Girls (MMIWG). “Stolen Sisters” provides information about current colonial perspectives of Indigenous women and how they need to be addressed, reflected upon, and challenged. Through Indigenous Knowledge surrounding the traditional roles of women, the meaning of the word ‘woman’ in the Cree language, and telling the stories of Indigenous women, “Stolen Sisters” aim is to provide education to the collegial public. Interdisciplinary Dialogue Project.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: colonialism; indigenous peoples; National Inquiry into Missing and Murdered Indigenous Women and Girls